Eutocic delivery vs. cesarean section: a multicenter retrospective study of factors influencing cesarean rates in Robson groups 1, 2a, 3, and 4a across birth centers - Musicco, Alessandra; Sfregola, Gianfranco; Dicuonzo, Vincenzo; Bolgeo, Tatiana; Milone, Virginia; Dicuonzo, Grazia; Iovino, Paolo; Ruta, Federico (Frontiers in Medicine, 2025)
ObjectiveCesarean deliveries are increasing rapidly worldwide. Although their primary indication is when vaginal delivery is not feasible, there appears to be an overutilization of this procedure, even in the absence of clear medical or obstetric indications. This exposes women to short-term and long-term adverse outcomes. This study aimed to investigate factors associated with cesarean section (CS) in nulliparous and multiparous women undergoing spontaneous and induced labor, focusing on Robson groups 1, 2a, 3, and 4a in birth centers of the Apulia Region (Italy) in 2019.MethodsThis multicenter retrospective observational study used data from the Delivery Room Registers of 14 facilities in the Apulia Region in 2019, covering 14,331 women. Inclusion criteria were belonging to Robson groups 1, 2a, 3, or 4a. Exclusion criteria were stillbirths and deliveries occurring in ambulances or at home. The final sample consisted of 9,992 women. Multilevel binary logistic regression models were performed to assess the impact of Robson groups and their combinations on the likelihood of CS. Chi-squared and Fisher’s exact tests were used to examine the distribution of CS across facilities.ResultsAmong women with spontaneous labor, multiparity was protective against CS compared with nulliparity (OR = 0.44, p < 0.001). Similarly, in induced labor, multiparity remained protective (OR = 0.46, p < 0.001). Women undergoing induction were approximately four times more likely to deliver via CS compared with those in spontaneous labor (OR = 3.87, p < 0.001). Overall, multiparous women were substantially less likely to undergo CS compared with nulliparous women (OR = 0.18, p < 0.001). Significant variability in CS rates across facilities was observed for all Robson groups (p < 0.001).ConclusionNulliparity and induction of labor were strongly associated with increased risk of CS. These factors should be carefully considered in clinical decision-making to help reduce unnecessary CS and mitigate associated adverse health outcomes.